Thermal Analysis of Inclined Micro Heat Pipes - Sugumar, D.; Tio, Kek-Kiong (2006)
The effect of gravity is investigated for the case of inclined-triangular- and trapezoidal-shaped micro heat pipes (MHPs). The study is limited to the case of positive inclination, whereby the condenser section is elevated from the horizontal position. The results show that the axial distribution of the liquid phase is changed qualitatively. While the liquid distribution still increases monotonically starting from the evaporator end, it reaches its maximum value not at the condenser end but at a certain point in the condenser section, beyond which the liquid distribution decreases monotonically. This maximum point, where potentially flooding will first take place, results from the balance between the effects of gravity, and the heat load on the MHPs. As the liquid distribution assumes its greatest value at the maximum point, a throat-like formation appears there. This formation is detrimental to the performance of MHPs, because it hinders, and at worst may block, the axial flow of the vapor phase. The results also show that the maximum point occurs further away from the condenser end for a triangular-shaped MHP compared to a trapezoidal-shaped MHP.